In vitro hypocholesterolemic potential of marine polysaccharides - Silva, Inês Maria Vaz (2022)
The prevalence of high cholesterol levels in the blood of the population translates in a mortality and morbidity index with high human and economic costs, being highly important to find new strategies to mitigate this problem. One way to reduce cholesterol levels in blood is to diminish its bioaccessibility, this is, decrease the amount that is emulsified in the intestinal lumen with the help of bile salts and thus available to be absorbed. In this work marine origin polysaccharides with different structural characteristics were explored, evaluating its hypocholesterolemic potential in an in vitro simplified intestinal model, as well as possible mechanisms of action. From brown algae Saccharina latissima, two types of polysaccharides were fractioned and structurally characterized, the laminarans (neutral) and fucose-containing sulphated polysaccharides (negatively charged). Chitosan (a positively charged polysaccharide) was also studied, which is a polysaccharide obtained from the deacetylation of chitin from crustaceous shells. The obtained results showed that the low molecular weight chitosan was the most promising polysaccharide, followed by the commercial fucoidan, in the reduction of cholesterol’s bioaccessibility, promoted by the sequestration of bile salts, whereas the other polysaccharides did not show a significant effect. To understand if other mechanisms of action were involved in the hypocholesterolemic effect of the marine origin polysaccharides, the viscosities of the most effective polysaccharides in reduction of cholesterol solubility were evaluated. In the concentration ranges studied, chitosan revealed higher viscosity compared to the commercial fucoidan. However, the diffusion coefficient evaluated by DOSY, which compared the solution in the presence and absence of chitosan, did not show significant alterations at the concentration used. This indicate that chitosan does not affect significatively the diffusion of bile salts micelles with cholesterol in the intestinal lumen, discarding this mechanism. Zeta-potential allowed to verify that at the physiologic pH used in the in vitro cholesterol solubility assays, the chitosan had positive charge, reinforcing the possibility of negatively charged bile salts sequestration by electrostatic interaction, corroborated by NMR quantification. Despite the negative character of fucoidan due to the sulphates groups and uronic acids, it has also capacity to sequestrate bile salts, contrary to what was observed with the laminarans (neutral), highlighting the possibility of hydrophobic interactions between bile salts and polysaccharides, depending on their structural nature. The present work allowed to identify that chitosan and fucoidans as potential to be used as hypocholesterolemic agents, detailing the possible mechanisms of action which can be useful for the design of functional foods with properties in reduction of cholesterol absorption that can have high impact in the society, namely in health and economy.